Bimbingan Kesehatan Tentang Seksualitas, HIV/AIDS dan NAPZA untuk Meningkatkan Pengetahuan dan Sikap Remaja Di Sekolah Menengah Pertama, Kecamatan Mengwi Badung Tahun 2018 - Ni Ketut Somoyani; Gusti Ayu Surati; Ni Nyoman Budiani; I Komang Lindayani; IGAA Novya Dewi (Poltekkes Kemenkes Denpasar, 2019)
Teen life is a life that is decisive for their future life. Indonesian youth are currently experiencing rapid social change from traditional society to modern society, which also alters their norms, values and lifestyles. These have resulted in increased adolescent vulnerability to various illnesses, particularly those related to sexual and reproductive health, including an increased threat to HIV / AIDS. The purpose of community service is to improve the knowledge and attitude of junior high school in District Mengwi Badung on Sexuality, and HIV / AIDS and Drugs. The activity target is 80 students of class VIII. The method used is health guidance with lectures, frequently asked questions and small group discussions. Improvement of youth knowledge and attitude was obtained from the result of pre test and post test questionnaire. The average pre-test value of knowledge before the highest guidance is at Public Junior High School 4 Mengwi with an average of 64, and the lowest in Public Junior High School 3 Mengwi with an average of 57. The average post-test value of knowledge after the highest guidance is in Public Junior High School 4 Mengwi with an average of 85 and the lowest in Junior High School 3 Mengwi with an average of 78. Assessment of adolescent attitudes before guidance in the fourth State Junior High School in Regency Mengwi: shows most say disagree if sexual education is done early. Most responded that authoritarian parents were the triggers of teenagers behaving deviantly like promiscuity and drug addicts. Approximately 60% -65% stay away if there are friends who are HIV positive. Assessment of adolescent post-guiding attitudes in the four State Junior High Schools in Mengwi Subdistrict: shows most agreed if sexual education is done early on. Most responded that authoritarian parents were the triggers of teenagers behaving deviantly like promiscuity and drug addicts. Most do not stay away if there are friends who are HIV positive. The conclusion of this activity that the knowledge and attitude of adolescents in State Junior High School Mengwi Badung District peningakatan from before and seseudah conducted health guidance about sexuality, HIV / AIDS and drug.Keywords : knowledge, attitude, teenager, adolescents, sexuality, HIV / AIDS and drug